Analisis Of Factors Related to Open Defecation Behavior in Punjul Village Plosoklaten District Kediri Regency - Eka Yuliati; Ardi Bastian (Universitas STRADA Indonesia, 2021)
Open defecation is one of major public health problem in Kediri regency. Data from the UPTD Puskesmas Pranggang shows that as many as 885 households in Punjul village do not have latrines. This study aims to analyze the associated factors of open defecation behavior in Punjul Village, Plosoklaten District, Kediri Regency. This study used a quantitative method with a cross sectional approach. This research was conducted in Punjul Village, Plosoklaten District Kediri Regency. Using simple random sampling technique, the number of sample was 93 respondents. Data analysis method was bivariate analysis using the chi-square test. The research finds that only one variable has no correlation on open defecation behaviour while the rest variables show significant association. Education has no correlation with open defecation behavior (p = 0.059, RP = 1.424). While other variable shows significant association; occupation (p = 0.025, RP = 1.985), income (p = 0.001, RP = 1.944), distance between houses and rivers (p = 0.007, RP = 0.307), attitudes towards regulations (p = 0.000, RP. = 2,710), community habits (p = 0,000, RP = 8,049), latrine ownership (p = 0,000, RP = 4,785). The most of open defecation is caused by uncertain income in Punjul Village so it is difficult to have a proper toilet. The close distance between the house and the river makes people prefer to defecate in the river. Community habits that have become a tradition / culture (passed down) from parents to defecate in the river. Only a few people who have healthy latrines. So, it is hoped that the public health center and the local government will conduct more frequent education to reduce open defecation, as well as provide an example for triggering healthy latrines by building public toilets.